1992
DOI: 10.1007/bf00942236
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social support and maternal behaviors and attitudes: A meta-analytic review

Abstract: Used meta-analysis to analyze 66 studies that evaluated the relationship between social support available to the mother and maternal behaviors and attitudes. Investigators sampled relatively homogeneous populations of white, middle-class, married mothers of young children without physical or mental disabilities. A variety of instruments were used to assess key study variables. Significant correlations existed between both emotional and material support and maternal behaviors. Implications of these findings for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Our findings revealed that if a parent feels well supported, they also feel that they are doing a better job at child care tasks and report having increased opportunities to engage in activities with their child. An association between social support and parenting behaviour is reported in the general parenting literature (Andresen & Telleen, 1992;Attree, 2005;Belsky, 1993;McLoyd, 1990) and in literature on parents with intellectual disability Willems, de Vries, Isarin, & Reinders, 2007). In particular, the current study expands on the work of Feldman et al (2002), who found that social support and parenting stress were negatively correlated for mothers with intellectual disability and that satisfaction with social support was positively correlated with a mother's positive interactions with her child.…”
Section: Discussionmentioning
confidence: 53%
“…Our findings revealed that if a parent feels well supported, they also feel that they are doing a better job at child care tasks and report having increased opportunities to engage in activities with their child. An association between social support and parenting behaviour is reported in the general parenting literature (Andresen & Telleen, 1992;Attree, 2005;Belsky, 1993;McLoyd, 1990) and in literature on parents with intellectual disability Willems, de Vries, Isarin, & Reinders, 2007). In particular, the current study expands on the work of Feldman et al (2002), who found that social support and parenting stress were negatively correlated for mothers with intellectual disability and that satisfaction with social support was positively correlated with a mother's positive interactions with her child.…”
Section: Discussionmentioning
confidence: 53%
“…Crnic et al . 1983; Andresen & Telleen 1992; Suarez & Baker 1997). For example, Hashima and Amato (1994) conducted a secondary analysis of data from over 1000 parents with children less than 5 years of age participating in the US National Survey of Families and Households.…”
Section: Introductionmentioning
confidence: 99%
“…Social support can also come from a variety of sources. In both predominantly White and predominantly Latina samples, general social support has been shown to reduce maternal psychological distress (Collins, Dunkel‐Schetter, Lobel, & Scrimshaw, ), improve maternal self‐efficacy (Isabella, ; Levy‐Shiff, Dimitrovsky, Shulman, & Har‐Even, ), positively impact maternal parenting (Andresen & Telleen, ), and improve child physical and behavioral health outcomes, including promoting child compliance and reducing behavior problems (Andresen & Telleen, ; Collins et al., ).…”
mentioning
confidence: 99%